Konseling Kelompok Teknik Desensitisasi untuk Mengatasi Ketakutan Akan Kematian Lansia - Virera, Dinda Rossa Aldyan; Lestari, Indah (Universitas Muria Kudus, 2024)
Elderly people often face the fear of death (thanatophobia) which reduces the quality of life. A qualitative descriptive approach was used to analyze changes in participants' perceptions, anxiety levels, and emotional responses. This study evaluated the effectiveness of group counseling using desensitization techniques in reducing anxiety related to death in six elderly women aged 60-67 years at the Mulia Hati Elderly School. Based on the results of the needs assessment, participants showed a high level of anxiety. The intervention is carried out in stages through controlled exposure to the topic of death in a supportive group atmosphere. The results showed a significant reduction in anxiety levels, increased acceptance of death, and a more positive change in outlook. Emotional disorders such as difficulty sleeping and anxiety are also reduced. Group dynamics create social support that strengthens the effectiveness of desensitization. These findings prove that group counseling using desensitization techniques is effective in overcoming fear of death while improving the emotional quality of life of the elderly.Elderly people often face the fear of death (thanatophobia) which reduces the quality of life. A qualitative descriptive approach was used to analyze changes in participants' perceptions, anxiety levels, and emotional responses. This study evaluated the effectiveness of group counseling using desensitization techniques in reducing anxiety related to death in six elderly women aged 60-67 years at the Mulia Hati Elderly School. Based on the results of the needs assessment, participants showed a high level of anxiety. The intervention is carried out in stages through controlled exposure to the topic of death in a supportive group atmosphere. The results showed a significant reduction in anxiety levels, increased acceptance of death, and a more positive change in outlook. Emotional disorders such as difficulty sleeping and anxiety are also reduced. Group dynamics create social support that strengthens the effectiveness of desensitization. These findings prove that group counseling using desensitization techniques is effective in overcoming fear of death while improving the emotional quality of life of the elderly.Artikel ini dapat diakses secara terbuka dibawah lisensi CC-BYhttps://doi.org/10.24176/jkg.v3i2.1643